Using Wolbachia to control rice planthopper populations: progress and challenges - Guo, Yan; Shao, Jiayi; Wu, Yanxian; Li, Yifeng (Frontiers in Microbiology, 2023)
Wolbachia have been developed as a tool for protecting humans from mosquito populations and mosquito-borne diseases. The success of using Wolbachia relies on the facts that Wolbachia are maternally transmitted and that Wolbachia-induced cytoplasmic incompatibility provides a selective advantage to infected over uninfected females, ensuring that Wolbachia rapidly spread through the target pest population.Most transinfected Wolbachia exhibit a strong antiviral response in novel hosts, thus making it an extremely efficient technique. Although Wolbachia has only been used to control mosquitoes so far, great progress has been made in developing Wolbachia-based approaches to protect plants from rice pests and their associated diseases. Here, we synthesize the current knowledge about the important phenotypic effects of Wolbachia used to control mosquito populations and the literature on the interactions between Wolbachia and rice pest planthoppers. Our aim is to link findings from Wolbachiamediated mosquito control programs to possible applications in planthoppers.